The Competence of Personality Preservice Teacher Based on The Strengthening of Character Education - Mutiara Felicita Amsal (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
Personality competencies are one of the four competencies that the educators should have. LPTK is a college that will produce prospective teachers. This study aims to improve the competence of the personality of the prospective teacher through the strengthening of character education. The research method used is a mixed method, which is using quantitative method to see the effect and qualitative methods to describe the data of the research. Based on the results of the research, there are six aspects of strengthening the character education associated with the personnel competence of prospective teachers, namely: 1) The attitude of nationalism and patriotism, 2) appreciates the difference, 3) prioritizing the appealing, 4) stressful and authoritative attitude, 5) discipline attitude, and 6) calls of the soul. The sixth of this aspect is included in the character of strengthening the character education to improve the ability of personality student personnel prospective teachers.This model of characterizing strengthening can be used for learning in college science, especially the primary education of the school element teacher concludes future candidates.